The origins and subsequent development of Administration Boards - Humphries, Richard G (Rhodes University, Faculty of Humanities, Department of Political Studies, 1983)
Until the introduction of administration boards in 1972-1973, the responsibility for administering the urban black townships in "white" South Africa was vested with the municipalities as agents of the Department of Bantu Administration and Development. The establishment of administration boards to replace the municipalities' Non-European Affairs Departments reflected the determination of the Department of Bantu Administration and Development to secure tighter direct control over the implementation of policy, particularly that affecting influx control and labour regulation. The decision to end municipal control was made after the report of the Van Rensburg Inter-Departmental Committee of Inquiry into Control Measures, which reported in 1967. The report's concern that influx control was not working as intended, coupled with doubts about the political autonomy of Opposition controlled municipalities, which dated back to the 1950s, were the major reasons for the introduction of administration boards.
Keywords: South Africa -- Politics and government -- 20th century; Influx control -- South Africa; Public administration -- South Africa